Investigation of Social education from the perspective of teachers and the theoretical foundations of fundamental change in the Islamic Republic of Iran - Ali Shiravani Shiri; Zahra ASkari (Islām va ̒ulūm-i ijtimā̒ī, 2021)
The purpose of the present study is to investigate the understanding of the theoretical foundations of fundamental development in the formal and public education system of the Islamic Republic of Iran and teachers of social education.Data were collected through qualitative paradigm in two ways: documentary and interview. The documents included the theoretical foundations of fundamental change . The study sample in the interview section was the first high school teachers in the two districts of Shiraz. The researchers studied and analyzed the data using a descriptive-interpretive approach and based on inductive content analysis. According to the findings of the study, It can be said that there are similarities between the two views on the limits and scope of social education. In both perspectives, attention is paid to the development of communication skills, observance of norms and rules. a survey of teachers' views shows that their view of social education is based on personal experience and studies they have had.